Endoscopic Resection of Sinonasal Hemangiopericytoma following Preoperative Embolisation: A Case Report and Literature Review - Georg J. Ledderose; Donata Gellrich; Markus Holtmannspötter; Andreas Leunig (Case Reports in Otolaryngology)
Objectives. Hemangiopericytoma is a rare tumor entity deriving from pericytes. Less than 5% of hemangiopericytoma occur in the nasal cavity and are characterised by a rather benign nature with low tendency of metastasis. However, as the recurrence rate in the literature ranges from 9.5% to 50%—depending on the length of followup—a radical surgical resection is considered as the gold-standard treatment. Only a few years ago, a wide external approach, usually via lateral rhinotomy or Caldwell-Luc, was performed. Endoscopic techniques were regarded as appropriate for small low-vascularised tumors only. Methods. We present the case of a 64-year-old patient with an extended sinonasal hemangiopericytoma, who was successfully treated by an endoscopic controlled endonasal tumor resection after embolisation with Onyx. Further, to support the new treatment option, we review the literature concerning all features of sinonasal hemangiopericytomas and their therapeutical management. Results/Conclusion. Onyx, which has not been described in the context of hemangiopericytoma yet, is a very effective embolic agent for a preoperative embolisation of sinonasal hemangiopericytoma allowing a safe endoscopic surgery.